Electrodegradation of tetracycline using stainless steel net electrodes: Screening of main effective parameters and interactions by means of a two-level factorial design - Foroughi, Maryam; Arezoomand, Hamid Reza Soheil; Rahmani, Ali Reza; Asgari, Ghorban; Nematollahi, Davood; Yetilmezsoy, Kaan; Samarghandi, Mohammad Reza (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2017)
Performance of electrodegradation process using stainless steel net electrodes was explored for removal of tetracycline (TC) from synthetic wastewater in a laboratory batch study. Main effects of various operating parameters, such as initial TC concentration (20 and 100 mg/L), reaction pH (3.0 and 9.0), current density (4.1 and 17.1 mA/cm(2)), agitation speed (250 and 750 rpm), and electrolysis time (20, 50, and 80 min), and their interactions on the TC removal efficiency, were optimized by means of a five-factor and two-level factorial experimental design methodology. The significance of responses obtained from the proposed design (sixteen experimental runs under batch mode conditions) was statistically evaluated by preparing a Pareto chart, half-normal probability plot, and plots of main effects and their interactions (herein referred to as Factions) within the framework of the analysis of variance (ANOVA). The statistical results corroborated with 95% certainty that TC concentration, pH, and current density showed the largest effects (absolute values) on the TC removal efficiency. Besides the most effective Factions, a sodium sulfate (used as supporting electrolyte) dose of 1 g/200 cc was determined as the optimum value for the studied process. Under the conditions of an initial TC concentration=20 mg/L, a reaction pH=3.0, current density=17.1 mA/cm(2), an agitation speed=250 rpm, and an electrolysis time=20 min, about 70% of TC could be successfully removed from the simulated wastewater. Findings of this experimental study clearly confirmed the applicability of the electrodegradation process for the removal of a broad spectrum antibacterial agent like TC, and also demonstrated the effectiveness of the factorial design methodology before transferring the obtained experimental knowledge for a full-scale facility.
Keywords: Electrodegradation; Screening; Factorial Experimental Design; Stainless Steel Nets; Supporting Electrolyte; Tetracycline; WASTE-WATER TREATMENT; RESPONSE-SURFACE METHODOLOGY; OIL MILL EFFLUENT; ELECTROCHEMICAL OXIDATION; ACTIVATED CARBON; AQUEOUS-SOLUTION; IRON ELECTRODES; REMOVAL; OPTIMIZATION; EXTRACTION; Chemistry; Engineering